Šport med telesno kulturo in kulturo telesa - Macura, Dušan (Šport (Ljubljana), 2021)
Pre-culture (gathering, agriculture, hunting and cattle breeding) as a self-preservation intervention of the body into its environment has “developed” over time into meta-culture (intervention into the body, not for preservation purposes, but to increase the body’s performance and to transfigure it). In this sense, through activation of physical abilities, physical culture is the primary “culturation” of the natural conditions of survival, while culture of the body is the “perfection” of physical abilities in the broadest sense (manual work, gesticulation, speech, singing, drawing etc. as physical activities). Modern sport, in this relation, plays a contradictory role. On the one hand, it preserves the original physical abilities (and thus the original body constitution), while on the other, it resists interventions in abilities and body constitution, bearing in mind that its resistance grows weaker. At the same time, this contradictoriness is one of the main reasons for the irresistible attractiveness of sport (since man is by nature a contradictory figure in the reality as such). Moreover, the core essence of (archaic and modern) sport, regarding competitive results, has remained unchanged (from survival to the cult of winner)*.
Keywords: body; filozofija športa; narava; nature; philosophy; physical culture; safety; sport; šport; telesna kultura; telo; varnost; vivacity; živost